Effect of galvanic vestibular stimulation applied at the onset of stance on muscular activity and gait cycle duration in healthy individuals - Abbariki, Faezeh; Mikhail, Youstina; Hamadjida, Adjia; Charron, Jonathan; Mac-Thiong, Jean-Marc; Barthélemy, Dorothy (Frontiers in Neural Circuits, 2023)
Locomotion requires the complex involvement of the spinal and supraspinal systems. So far, the role of vestibular input in gait has been assessed mainly with respect to gait stability. The noninvasive technique of galvanic vestibular stimulation (GVS) has been reported to decrease gait variability and increase gait speed, but the extent of its effect on spatiotemporal gait parameters is not fully known. Objective: Characterize vestibular responses during gait and determine the influence of GVS on cycle duration in healthy young participants. Methods: Fifteen right-handed individuals participated in the study. Electromyography (EMG) recordings of the bilateral soleus (SOL) and tibialis anterior muscles (TA) were performed. First, to determine stimulation intensity, an accelerometer placed on the vertex recorded the amplitude of the head tilts evoked by the GVS (1–4 mA, 200 ms) to establish a motor threshold (T). Second, while participants walked on a treadmill, GVS was applied at the onset of the stance phase during the treadmill gait with an intensity of 1 and 1.5 T with the cathode behind the right (RCathode) or left ear (LCathode). EMG traces were rectified, averaged (n = 30 stimuli), and analyzed. Latency, duration, and amplitude of vestibular responses as well as the mean duration of the gait cycles were measured. Results: GVS mainly induced long-latency responses in the right SOL, right TA and left TA. Only short-latency responses were triggered in the left SOL. Responses in the right SOL, left SOL and left TA were polarity dependent, being facilitatory with RCathode and inhibitory with LCathode, whereas responses in the right TA remained facilitatory regardless of the polarity. With the RCathode configuration, the stimulated cycle was prolonged compared with the control cycle at both 1 and 1.5 T, due to prolonged left SOL and TA EMG bursts, but no change was observed in right SOL and TA. With LCathode, GVS did not modify the cycle duration. Conclusion: During gait, a brief, low-intensity GVS pulse delivered at the right stance onset induced mainly long-latency polarity-dependent responses. Furthermore, a RCathode configuration increased the duration of the stimulated gait cycle by prolonging EMG activity on the anodic side. A similar approach could be explored to influence gait symmetry in individuals with neurological impairment.